Software de auxílio no ensino para dimensionamento de elementos estruturais de concreto armado - Turpo, Ray Paul Cotacallapa (2020)
In this work, the development of assistive software for the design of reinforced concrete elements according to NBR 6118: 2014 is presented, using the programming language C # and Xamarin, in order to improve the teaching-learning process. Considering that the teaching of reinforced concrete is important in the training of the Civil engineer. In addition, computers and cell phones are resources to promote the transfer of information and facilitate the process of building knowledge. The software was developed for both computer and mobile use, for reinforced concrete design topics for simple normal bending beams, shear design and column design. The software features are: to present a summary of the results and a detailed calculation guide.